Primate play laughing: a comparison between immature great apes and humans (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: playful facial expressions; contact physical play; play face homology; chimpanzees; Pan troglodytes